Fuzzy Logic Based Algorithm for Electrical Load Management in Touring Buses - Butevski, Boris; Latkoska, Vesna Ojleska; Stavrov, Dushko (International Conference on Systems, Signals, and Image Processing (Online), 2023)
This paper presents a fuzzy logic (FL) approach for electrical load management in touring buses. The backwards simulation modeling technique is utilized, based on the VECTO drive cycle to obtain the powertrain model. The FL algorithm determines the applied voltage on the battery, based on the Brake Specific Fuel Consumption (BSFC) map and the battery state of charge. The outcome of this strategy, in terms of fuel consumption, is compared to the conventional battery charging approach. Based on the simulation results, we conclude that the proposed algorithm improves the fuel economy, compared to the conventional method.